Cultural Diplomacy Efforts of The Indonesian Embassy in Seoul to Promote The Indonesian Language in South Korea - Shavira Febrianti Noor Tiara (Universitas Muhammadiyah Malang, 2022)
This study aims to understand and analyze the cultural diplomacy efforts of the Indonesian Embassy in Seoul in developing the Indonesian language in South Korea. The increasingly positive bilateral relations between Indonesia and South Korea have an impact on the popularity of the Indonesian language, which is starting to be in demand in South Korea. This is an effective step for the Indonesian Embassy in Seoul to increase its efforts to promote and develop the Indonesian language in South Korea through facilities and Indonesian language learning programs for South Korean people who are interested in learning Indonesian in South Korea. Therefore, the theoretical basis used in this research is Cultural Diplomacy by Tulus and Wahyuni, and Soft Power by Joseph Nye. Based on this theory, the author will analyze the forms and benefits of developing the Indonesian language in South Korea. The Researcer uses primary and secondary data sources through interviews and literature studies with electronic media such as journals, the internet, mass media, and newspapers. The results showed that the cultural diplomacy of the Indonesian Embassy in Seoul through the development of the Indonesian language could help and increase the interest of the South Korean people in learning the Indonesian language, as well as have a positive impact on improving bilateral relations between Indonesia and South Korea through cultural instruments.